Transmitter modulation performance analysis - Ang, Zhi Hong (2009)
Satellites have been widely developed for education, earth observation, constellation operation and etc. Satellite tracking and orbit determination are essential elements of most satellite missions. The knowledge of the spacecraft position at any time is a requirement for communication and planning.